1998
DOI: 10.1038/nsb0198-60
|View full text |Cite
|
Sign up to set email alerts
|

Complementary sets of noncanonical base pairs mediate RNA helix packing in the group I intron active site

Abstract: Helix packing is critical for RNA tertiary structure formation, although the rules for helix-helix association within structured RNAs are largely unknown. Docking of the substrate helix into the active site of the Tetrahymena group I ribozyme provides a model system to study this question. Using a novel chemogenetic method to analyze RNA structure in atomic detail, we report that complementary sets of noncanonical base pairs (a G.U wobble pair and two consecutively stacked sheared A.A pairs) create an RNA heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
92
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 38 publications
7
92
0
2
Order By: Relevance
“…1,2,6,14,65,66 Many interactions determine the structures and thermodynamic stabilities of internal loops with tandem GA pairs. The data here provide benchmarks to test computational approaches for understanding the relative importance of the various interactions and thus provide the power to predict structure, stability, and dynamics for other internal loops.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,6,14,65,66 Many interactions determine the structures and thermodynamic stabilities of internal loops with tandem GA pairs. The data here provide benchmarks to test computational approaches for understanding the relative importance of the various interactions and thus provide the power to predict structure, stability, and dynamics for other internal loops.…”
Section: Discussionmentioning
confidence: 99%
“…This large catalytic RNA leaves products with termini opposite to the HDV ribozyme and it has been shown that both the geometry and minor groove of the G d U wobble pair at the active site are important for positioning functional groups for RNA substrate recognition (Barfod and Cech 1989;Doudna et al 1989;Downs and Cech 1994;Knitt et al 1994;Cate and Doudna 1996;Strobel et al 1998;Adams et al 2004;Golden et al 2005). In addition, crystal (Cate and Doudna 1996) and NMR (Allain and Varani 1995;Kieft and Tinoco 1997) structures revealed that the active site G d U wobble pair, as well as tandem G d U wobble pairs in other parts of the ribozyme, FIGURE 1.…”
Section: Introductionmentioning
confidence: 99%
“…Four potential long-range RNA-RNA interactions (see inset in Fig. 2) appear to be exclusively found in the +P5ext introns, including interactions between (1) GAAA tetraloops in L5b and L9, and 11-nt receptors in P6 and J5/5a, respectively (Costa and Michel 1995;Ikawa et al 2000b), (2) the A-rich bulge and the P4 paired element (Cate et al 1996;Ikawa et al 2002), and (3) the highly conserved A in J4/5 that is involved in defining the universally conserved G·u wobble pair in P1 (Michel and Westhof 1990;OrtolevaDonnelly et al 1998;Strobel et al 1998). The GAAA/11-nt receptor interaction between L9 and the P5 region might, however, be replaced by other types of RNA-RNA contacts (e.g., Jaeger et al 1994;Lehnert et al 1996).…”
Section: Secondary Structure and Self-splicing Of Fungal S788 Intronsmentioning
confidence: 99%